Environment-friendly strippable seam filling agent as well as preparation method and use method of environment-friendly strippable seam filling agent
By using a two-component seam filler composed of polyasparticle and modified isocyanate, the problem of difficult application of existing epoxy coil seam filler in narrow and low temperature environments is solved, and efficient filling and easy filling are achieved The peeling effect improves construction efficiency and bonding strength.
Patent Information
- Application Number
- CN202411667061.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
AI Technical Summary
The existing epoxy coil caulking agent has complicated steps to paste textured paper during construction, and the high viscosity leads to difficulty in application in narrow and low temperature environments, and the curing reaction is greatly affected by temperature, resulting in low construction efficiency and Problem of long curing time.
Using a two-component seam filler composed of polyasparticle and modified isocyanate, the chain segment structure after reaction curing is improved by introducing polyol α and polyol β, so that it can still maintain good results in low temperature environments. The filling effect can be easily peeled from the epoxy coil surface layer after curing.
It realizes the ability to fill efficiently in narrow gaps of 0.5 to 1mm and low temperature environments, and can be easily peeled off after the caulking is completed, avoiding the step of pasting textured paper, improving construction efficiency, and ensuring the side of the epoxy coil effective bonding.
Smart Images

Figure CN119391352A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy coiled materials, and in particular to an environmentally friendly peelable fine seam filler and a preparation and use method thereof. Background Art
[0002] At present, domestic caulking products are mainly made of epoxy and polyurethane, and the gaps are mostly 2-3mm wide. During the construction process, the gaps often reach 3-4mm due to actual conditions. In addition, the caulking level is also affected by the skills of the construction personnel, and the smoothness of the gaps obtained by manual caulking is often not particularly ideal.
[0003] The epoxy coil sealant currently used is a two-component epoxy-based sealant, which is characterized by the fact that both the coil and the sealant are epoxy systems, with good compatibility between the materials, providing high bonding strength and good water resistance. However, there are the following problems in the application: First, the construction method is cumbersome. Before construction, it is necessary to neatly paste masking tape along both sides of the seam to achieve the purpose of not contaminating the epoxy coil when the residual material is filled during the caulking. After the caulking work, the masking tape needs to be peeled off. Therefore, the construction efficiency is greatly reduced in large-scale construction work. Second, the viscosity of the epoxy-based sealant currently in service is relatively large. During the winter construction process, the sealant needs to be heated to achieve the purpose of reducing viscosity, and the sealant with a large viscosity is not conducive to filling narrow gaps, which undoubtedly increases the difficulty of construction. Third, the cross-linking reaction rate of epoxy resin is greatly affected by temperature, which is not conducive to the occurrence of its curing reaction in a low temperature construction environment, which results in the equipment and people being unable to enter the paved ground in a short time after the caulking work is completed.
[0004] Based on the above problems, it can be found that the existing epoxy coil sealant cannot be used in narrow gaps and low temperature environments due to performance defects; therefore, there is an urgent need for an epoxy coil sealant with more comprehensive performance and suitable for a wide range of applications. Summary of the invention
[0005] The present invention provides an environmentally friendly peelable fine seam filler and a preparation and use method thereof. The environmentally friendly peelable fine seam filler prepared by the present invention can be easily peeled off from the epoxy surface layer without pasting masking tape during construction, and the filling width can be as low as 0.5 to 1 mm; it is waterproof and stain-resistant, has no harmful irritating odor, and is suitable for construction conditions with high requirements for aesthetics and tight construction period.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention provides an environmentally friendly peelable fine seam filler, which is composed of a component A and a component B in a weight ratio of (0.95-1.05), wherein the component B is a modified isocyanate; wherein, in parts by weight,
[0008] The composition of component A is:
[0009]
[0010]
[0011] The present invention utilizes the steric hindrance effect caused by the -X group in the polyaspartic acid ester, so that the reaction rate of the A component and the B component is controllable and the adhesion is moderate.
[0012] On this basis, polyol α and polyol β are introduced and compounded to improve the segment structure after the reaction and curing of component A and component B, so that the segment structure after curing has a certain toughness. In this way, when the epoxy coil is caulking, the bonding strength between the caulking agent and the inorganic material section on the side of the epoxy coil can be increased, but the adhesion between the caulking agent and the epoxy material on the surface of the epoxy coil is not strong, so that the excess caulking agent can be easily peeled off when processing in the later stage.
[0013] The environmentally friendly peelable fine crack filler prepared by the environmentally friendly peelable fine crack filler formula provided by the present invention has moderate curing time, curing speed, surface drying time, high bonding strength and strong peeling property, and has been proved to have good filling effect for narrow gaps of 0.5 to 1 mm, and can be easily peeled off from the surface layer of epoxy coil after the filling is completed and can ensure effective bonding with the side of the epoxy coil. In addition, the environmentally friendly peelable fine crack filler still shows good filling effect in a low temperature environment (0 to 5°C) and has a short curing time, which is due to the selection of polyaspartic acid ester and polyol α and polyol β.
[0014] Preferably, the mass ratio of component A to component B is 1:1.
[0015] Preferably, the polyaspartic acid ester is F5240 polyaspartic acid ester.
[0016] There are X groups and R groups in the structural formula of polyaspartic acid ester. Different X groups and R groups form different types of polyaspartic acid ester. Among them, when the X group contains a large steric hindering group such as a benzene ring, it will lead to a slow reaction; when the polarity of the group in the X group is greatly different from that of the epoxy resin, it will lead to strippability. The preferred F5240 model in this application can help improve the strippability of the sealant.
[0017] Preferably, the polyol α is a polyether polyol with a molecular weight of 400 to 2000, and the polyol β is a polyester polyol with a molecular weight of 1000 to 2000.
[0018] More preferably, the polyol α is a polyether polyol with a molecular weight of 725, and the polyol β is a polyester polyol with a molecular weight of 1000.
[0019] Preferably, the polyether polyol is one or more of polyoxypropylene glycol and polytetramethylene glycol, and the polyester polyol is one or more of polycarbonate glycol and poly-ε-caprolactone glycol.
[0020] More preferably, the polyether polyol is polyoxypropylene diol, and the polyester polyol is polycarbonate diol.
[0021] Preferably, the filler is fumed silica with an average particle size of 5 to 8 μm.
[0022] As the only solid raw material in the formula of environmentally friendly strippable slit filler, fumed silica can ensure that the entire filler system can flow into the slits during caulking.
[0023] Preferably, the leveling agent is a silicone additive.
[0024] More preferably, the organosilicon additive is polyether-modified polysiloxane.
[0025] Preferably, the filler is ethylene glycol diacetate.
[0026] It can ensure that the A component and the B component (0.95-1.05) are mixed without reacting with polyaspartic acid ester, polyol α and polyol β.
[0027] Preferably, the color paste is an oily color paste.
[0028] The present invention also provides a method for preparing an environmentally friendly peelable fine-crack filler, comprising: stirring and mixing polyaspartic acid ester, polyol α, polyol β, defoamer, leveling agent, filler and filler for 30 to 60 minutes, adding color paste, stirring and mixing again, and standing for 20 to 30 minutes to obtain component A; weighing modified isocyanate at a mass ratio of component A to component B of 1:1 to obtain component B.
[0029] The present invention also provides a method for using an environmentally friendly peelable fine-crack filler, comprising: mixing component A and component B of the environmentally friendly peelable fine-crack filler, filling the mixture into a 0.5-1 mm gap of an epoxy coil, and after curing for 2-3 hours, peeling off the cured environmentally friendly peelable fine-crack filler on the surface of the epoxy coil to complete the filling.
[0030] Therefore, the present invention has the following beneficial effects:
[0031] (1) The environmentally friendly peelable fine seam filler provided by the present invention has a low static viscosity and a high dynamic viscosity, and can be used to fill the gaps in epoxy coils of 0.5 to 1 mm. After the filling is completed, it can be easily peeled off from the surface layer of the epoxy coil and can ensure effective bonding with the side of the epoxy coil.
[0032] (2) The environmentally friendly peelable fine seam filler provided by the present invention still exhibits a good filling effect in a low temperature environment (0-5°C); the process and speed of the cross-linking reaction between polyaspartic acid ester and isocyanate are less affected by temperature, and even in winter, it can ensure that equipment and people can enter the paved ground four hours after the construction is completed.
[0033] (3) The environmentally friendly peelable fine seam filler provided by the present invention has a low bonding strength with the dense epoxy surface layer, which can save the step of pasting masking tape. After filling the seams, the remaining material can be directly and easily peeled off from the surface layer, but it can ensure effective bonding with the cut surface of the epoxy coil, and the bonding strength is greater than 5MPa, which meets the use requirements.
[0034] (4) The environmentally friendly peelable fine seam filler provided by the present invention is prepared from raw materials with low volatile organic matter, so that no irritating and harmful gases are generated after the floor is paved, thereby improving the environmental friendliness of the use of the filler. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is the preparation process diagram;
[0036] Figure 2 This is a welding strength test curve of the environmentally friendly peelable fine seam filler prepared in Example 1;
[0037] Figure 3 is a cross-sectional view of the caulking of the present invention;
[0038] Figure 4 This is a schematic diagram of the residual material stripping of Example 1. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific embodiments. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0040] The average particle size of the fumed silica in this part is 6 μm, which can be purchased from Jinan Zhongbei Fine Chemical Co., Ltd. F5240 polyaspartic acid resin, F524 polyaspartic acid resin, and F420 polyaspartic acid resin can be purchased from Shenzhen Feiyang Junyan Co., Ltd. Modified isocyanate and hexamethylene diisocyanate were purchased from Alibaba. Polyoxypropylene diol, molecular weight 725; polytetramethylene ether, molecular weight 1000; poly-ε-caprolactone diol, molecular weight 530, the above three diol substances were purchased from Shanghai Aladdin Biochemical Co., Ltd. Polycarbonate diol, molecular weight 1000, was purchased from Asahi Kasei Corporation. Amino-terminated polyether, molecular weight 2000, was purchased from Suzhou Xiangyuan Chemical Co., Ltd. 7010 defoamer and silicone-modified polyether leveling agent were purchased from BYK Chemical Co., Ltd. Ethylene glycol diacetate was purchased from Guangzhou Suixin Chemical Co., Ltd. Styrene-butadiene-styrene block copolymer was purchased from Kraton Chemical Products Co., Ltd., xylene was purchased from Longxing Chemical Co., Ltd., bisphenol A epoxy resin was purchased from Nan Ya Epoxy Resin Company, and polyamide curing agent was purchased from Yixin Materials Co., Ltd.
[0041] [Example]
[0042] Example 1
[0043] S1. Figure 1 As shown, weigh each raw material according to the formula in Table 1, and put the weighed F5240 polyaspartic acid ester resin (the general structure of polyaspartic acid ester is shown in Formula 1), polyoxypropylene glycol, polycarbonate diol, 7010 defoamer, polyether modified silicone additive, fumed silica and ethylene glycol diacetate into a batching barrel. Use a disperser to disperse the raw materials in the batching barrel for 45 minutes at a speed of 1200r / min, mix all the raw materials evenly, add color paste RAL7035, maintain the speed until the color paste RAL7035 is evenly dispersed, and let it stand for 20 minutes to eliminate bubbles generated during stirring to obtain component A.
[0044] S2. According to the mass ratio of component A to component B of 1:1, weigh the corresponding weight of modified isocyanate to obtain component B
[0045] S3. Load component A into one side of the 1:1 two-component hose and component B into the other side of the 1:1 two-component hose. After the liquid level is balanced, install the piston and seal the air outlet at the end. The hose adopts a cross-mixing nozzle to ensure that components A and B are evenly mixed when pumping.
[0046]
[0047] The structure of polyaspartic acid esters varies according to the type, in which the X group and the R group are different. The X group causes the reactive group -NH to be in a large steric package.
[0048] Example 2
[0049] This embodiment is basically the same as embodiment 1, except that the preparation is carried out according to the proportions of embodiment 2 in Table 1.
[0050] Example 3
[0051] This embodiment is basically the same as embodiment 1, except that the preparation is carried out according to the proportions of embodiment 3 in Table 1.
[0052] Table 1 Different ratios (parts by weight)
[0053]
[0054] Example 4
[0055] This embodiment is substantially the same as the embodiment 1, except that the "polyoxypropylene glycol" in the component A of the embodiment 1 is replaced by an equal amount of polytetramethylene ether glycol.
[0056] Example 5
[0057] This embodiment is substantially the same as the embodiment 1, except that the "polyester polyol A" in the component A of the embodiment 1 is replaced with an equal amount of poly-ε-caprolactone diol.
[0058] Comparative Example 1
[0059] This comparative example is basically the same as Example 1, except that: the ratio is, by weight, component A is 25 parts of styrene-butadiene-styrene block copolymer, 70 parts of xylene, 3 parts of color paste RAL7035 and 2 parts of fumed silica; component B is eliminated.
[0060] Comparative Example 2
[0061] This comparative example is basically the same as Example 1, except that: the ratio is, by weight, component A is 90 parts of bisphenol A epoxy resin, 5 parts of fumed silica, and 5 parts of color paste RAL7035; component B is 100 parts of polyamide curing agent.
[0062] Comparative Example 3
[0063] This comparative example is substantially the same as Example 1, except that the component A "F5240 polyaspartic acid ester resin" in Example 1 is replaced by an equal amount of F524 polyaspartic acid resin.
[0064] Comparative Example 4
[0065] This comparative example is substantially the same as Example 1, except that the component A "F5240 polyaspartic acid ester resin" in Example 1 is replaced by an equal amount of F420 polyaspartic acid resin.
[0066] Comparative Example 5
[0067] This comparative example is substantially the same as Example 1, except that the "polyoxypropylene diol" in component A of Example 1 is replaced with an equal amount of polycarbonate diol.
[0068] Comparative Example 6
[0069] This comparative example is substantially the same as Example 1, except that the "polycarbonate diol" in component A of Example 1 is replaced with an equal amount of polyoxypropylene diol.
[0070] Comparative Example 7
[0071] This comparative example is substantially the same as Example 1, except that the polytetramethylene furan ether and polyester polyol A in component A of Example 1 are replaced with equal amounts of amino-terminated polyether.
[0072] Comparative Example 8
[0073] This comparative example is substantially the same as Example 1, except that the modified isocyanate of component B in Example 1 is replaced by an equal amount of hexamethylene diisocyanate.
[0074] Comparative Example 9
[0075] This comparative example is substantially the same as Example 1, except that the weight portion of the modified isocyanate component B in Example 1 is replaced with 120 parts.
[0076] Comparative Example 10
[0077] This comparative example is substantially the same as Example 1, except that the weight portion of the modified isocyanate component B in Example 1 is replaced with 80 parts.
[0078]
Performance test
[0079] The indicator detection methods in this section are as follows:
[0080] ① The toughness test method refers to "GB / T 2567-2021 Test method for properties of resin castings". Prepare the test samples according to the method in the standard, and test the tensile strength and elongation at break.
[0081] ② The surface drying time test method refers to "GB1728-1979 Determination of Drying Time of Paint Film and Putty Film" to test the surface drying time of the sample.
[0082] ③ The welding strength with epoxy membrane refers to "GB 18173.1-2012 Polymer Waterproof Materials", prepare the test sample according to the method in the standard, and test the welding strength between the sealant and the epoxy membrane.
[0083] ④ Aesthetics is generally evaluated visually, mainly by observing the flatness of the caulking agent, the presence of bubbles, and whether there are burrs after the excess material is peeled off.
[0084] ⑤ Peelability generally refers to the ease of peeling from the surface layer of the epoxy membrane and the degree of residual surface layer of the epoxy membrane after peeling.
[0085] The environmentally friendly peelable fine seam fillers obtained in Examples 1 to 5 and Comparative Examples 1 to 10 were added to 15 groups of epoxy coils for performance testing. The results are shown in Table 2.
[0086] Each test is as follows: four pieces of 20cm×20cm epoxy membranes are spliced on the ground, and the gap between each piece of epoxy membrane is kept at 0.5mm. Figure 3 As shown, after cleaning the gap, ensure that the edges of the epoxy coil are aligned, then use a glue gun to apply the environmentally friendly peelable fine seam filler in the two-component hose in Example 1 to the gap, so that the environmentally friendly peelable fine seam filler completely covers the gap. After waiting for 20 minutes, use the back of the external corner seam knife to scrape along the gap once, and after another 10 minutes, use the same method to hang along the gap again. After curing for 3 hours, directly peel off the remaining material to complete the filling; among which, the peeling effect of Example 1 can be seen in Figure 4 .
[0087] Figure 2 The welding strength test results of the environmentally friendly peelable fine seam filler in Example 1, the welding width of the test sample is 50mm, the thickness is 1.530mm, the tensile rate during the test is 50mm / min, and the welding strength after the test is 8.9MPa. The welding strength test parameters of the remaining Examples 2 to 5 and Comparative Examples 1 to 10 are carried out with reference to Example 1, and the obtained welding strength results are recorded in Table 2.
[0088] Table 2 Performance comparison table
[0089]
[0090]
[0091] It can be seen from Table 2 that the environmentally friendly peelable fine gap fillers prepared by the present invention all show balanced and excellent performance. A careful comparison of the data results of Example 1 and Comparative Examples 1 to 4 shows that after replacing the main polyaspartic acid ester resin, the performance of the filler is attenuated to varying degrees. This shows that the steric effect caused by the -X group in the F5240 polyaspartic acid ester resin can help improve the surface drying speed and shorten the surface drying time.
[0092] In Comparative Examples 5 and 6, the compounding of polyether polyol and polyester polyol is cancelled, wherein Comparative Example 5 is a single polycarbonate diol, and its performance decay is more severe, and the elongation at break declines seriously, making the toughness of the sealant insufficient and very easy to crack. And from the comparison of the performance data of Example 1, Comparative Example 5 and Comparative Example 6, the performance of Example 1 is much higher than any index of Comparative Example 5 and Comparative Example 6, which shows that the synergistic effect between polyether polyol and polyester polyol can help to greatly improve the performance. In addition, when the polyol chain extender is changed to a polyether ammonia chain extender, the surface drying time will be significantly extended. This is because the molecular weight of the amino-terminated polyether is too large, resulting in a long curing time. Therefore, the choice of molecular weight also has a great influence on the role of the chain extender. The polyester polyol and polyether polyol selected in this application have moderate molecular weights, which can help the sealant maintain optimal performance.
[0093] The environmentally friendly peelable fine seam fillers obtained in Examples 1 to 5 and Comparative Example 2 were added to 6 groups of epoxy coils for low temperature performance testing. The results are shown in Table 3.
[0094] Each test is as follows: four pieces of 20cm×20cm epoxy membranes are spliced on the ground, and the gap between each piece of epoxy membrane is kept at 0.5mm. Figure 3 As shown, after cleaning the gap, ensure that the edges of the epoxy coil are aligned, then use a glue gun to apply the environmentally friendly peelable fine seam filler in the two-component hose in Example 1 to the gap, so that the environmentally friendly peelable fine seam filler completely covers the gap. After waiting for 20 minutes, use the back of the external corner seam knife to scrape along the gap once, and after another 10 minutes, use the same method to hang along the gap again. After curing for 3 hours, directly peel off the remaining material to complete the filling.
[0095] Table 3 Comparison of low temperature reaction performance
[0096]
[0097] It can be seen from Table 3 that the performance of the environmentally friendly peelable fine joint filler provided by the present invention at low temperature is compared with that of Comparative Example 2, which proves that the environmentally friendly peelable fine joint filler is less affected by temperature and can still be quickly cured and then paved in a relatively low temperature construction environment, which can greatly shorten the construction period.
Claims
1. An environmentally friendly peelable fine seam filler, characterized in that: The invention is composed of component A and component B in a weight ratio of (0.95-1.05):1, wherein component B is a modified isocyanate; wherein, in parts by weight, The composition of component A is:
2. The environmentally friendly peelable fine seam filler according to claim 1, characterized in that: The polyaspartic acid ester is F5240 polyaspartic acid ester.
3. The environmentally friendly peelable fine seam filler according to claim 1 or 2, characterized in that: The polyol α is a polyether polyol with a molecular weight of 400 to 2000, and the polyol β is a polyester polyol with a molecular weight of 1000 to 2000.
4. The environmentally friendly peelable crack stripping agent according to claim 3, characterized in that: The polyether polyol is one or more of polyoxypropylene glycol and polytetramethylene ether glycol, and the polyester polyol is one or more of polycarbonate glycol and poly-ε-caprolactone glycol.
5. The environmentally friendly peelable fine crack filler according to claim 1, characterized in that: The filler is fumed silica with an average particle size of 5 to 8 μm.
6. The environmentally friendly peelable fine crack filler according to claim 1, characterized in that: The leveling agent is an organic silicon auxiliary agent.
7. The environmentally friendly peelable fine crack filler according to claim 1, characterized in that: The filler is ethylene glycol diacetate.
8. The environmentally friendly peelable fine crack filler according to claim 1, characterized in that: The color paste is an oily color paste.
9. The method for preparing the environmentally friendly peelable fine seam filler according to any one of claims 1 to 8, characterized in that: include: The polyaspartic acid ester, polyol α, polyol β, defoamer, leveling agent, filler and filler are stirred and mixed for 30 to 60 minutes, and then the color paste is added, and the mixture is stirred and mixed again and then allowed to stand for 20 to 30 minutes to obtain component A; the modified isocyanate is weighed according to the mass ratio of component A to component B being (0.95 to 1.05):1 to obtain component B.
10. The method for using the environmentally friendly peelable fine seam filler according to any one of claims 1 to 8, characterized in that: include: After mixing the components A and B of the environmentally friendly peelable fine crack filler, fill them into the gap of 0.5-1 mm of the epoxy coil. After curing for 2-3 hours, peel off the cured environmentally friendly peelable fine crack filler on the surface of the epoxy coil to complete the filling.
Citation Information
Cited By
Joint mixture for aviation aircraft metal component and preparation method of joint mixture
CN120574557A